Preservation of Local Wisdom in the Era of Globalization: Case Study of Electricity Rejection in Naga Traditional Village - Indah Kristina Wulandari; Eneng Serli; Tia Ihsantiani; Ratna Wulan Munggarani; Dinna Daniati; Jajang Hendar Hendrawan (STKIP Taman Siswa Bima, 2025)
This study discusses the efforts to preserve local wisdom implemented by the Naga Traditional Village community in facing the challenges of globalization, especially through the decision to reject the use of electricity as a form of preserving cultural values and a simple lifestyle. The method used is a qualitative approach with case studies, obtained through direct interviews and field observations. The results of the study reveal that the Naga Village community does not close itself off from technological advances, but chooses to respond selectively to remain in line with customary norms. Efforts to preserve culture are carried out through the process of passing on values between generations, the central role of customary figures, and restrictions on the use of technology to maintain balance with the environment. These results indicate that the preservation of local culture can be carried out side by side with modernization as long as it maintains existing cultural principles.